Different wavelengths of laser: are they significant for treatment of denture stomatitis?: an in-vitro study - Mai Salah El-Din; Ahlam El-Sharkawy; Hams Abdelrahman; Kenda I. Hanno (BMC, 2024)
Abstract Background Denture stomatitis (DS) is an inflammatory disorder that affects the mucosal surface underneath the dentures and frequently causes oral mucosal irritation, discomfort, and altered taste perception, which prevents people from consuming enough nutrients. One of the main causes of DS is an overgrowth of the fungus Candida albicans (C. albicans). A possible alternative treatment for Candida infections is thought to be laser therapy. The aim of this study was to evaluate how different wavelengths of laser would affect growth and pathogenic properties of Candida albicans. Methods A concentration of 106 viable cells/ml of Candida albicans were used in the preparation process. Four groups were created from the specimens. Culturing of the control group was completed with no intervention. The other 3 groups received laser radiation for 60 seconds at a power of 1W. The 2nd and 3rd groups were irradiated with diode laser at a wavelength of 940 nm and 980 nm respectively. The 4th group was irradiated with Nd-YAG laser at a wavelength of 1064 nm. Turbidimetric growth was defined as variations in the optical density of fungal growth. These measures were made at three different times: baseline, 48 hours, and 72 hours. Results In both groups of diode laser, the growth of Candida albicans showed no remarkable differences at baseline, after 48 and 72 hours using a power of 1 W and duration of 60 seconds. The Nd-YAG group showed significant increase in optical density after 48 hrs then significant decrease after 72 hrs. The optical density values in the control group showed no notable difference between the control and diode study groups at different time periods. However, the Nd:YAG group showed a statistically significant difference compared to the control and the 2 diode laser groups. Conclusions Different laser parameters have a different effect on growth and pathogenic properties of Candida albicans. Diode laser therapy with wavelengths 940 and 980 nm used in continuous mode with power of 1 W for duration of 60 seconds can result in proliferation of Candida albicans instead of destroying them. Nd:YAG laser, used in pulsed mode, with power of 1 W for a duration of 60 seconds can be used to destroy Candida albicans and therefore, can be used as an effective treatment for denture stomatitis.